Genicular artery embolization for knee osteoarthritis: a systematic review with meta-analysis and cost-analysis - Aránzazu Hernández-Yumar; Yadira González-Hernández; Tasmania del Pino-Sedeño; Cristina Valcárcel-Nazco; Aythami de Armas-Castellano; Estefanía Herrera-Ramos; Julián Portero Navarro; Montserrat Carmona-Rodríguez; María Ximena Rojas-Reyes; María M. Trujillo-Martín (Gaceta Sanitaria, 2025)
Objective: To assess the effectiveness, safety, and cost-effectiveness of genicular artery embolization (GAE) for the treatment of mild or moderate knee osteoarthritis (KO) refractory to standard treatment, and/or severe KO in individuals not eligible for surgery. Method: We conducted a systematic review with meta-analysis, supplemented by a cost-analysis, comparing GAE and standard treatment, from the perspective of the Spanish National Health System (NHS) over a one-year time horizon. The health improvement required for GAE to be deemed cost-effective was quantified, considering a willingness-to-pay threshold of 25 000 €/quality-adjusted life year (QALY). Results: We included two randomized controlled trials in our analysis. Pain estimates showed inconsistent results, and no significant effects were observed for overall function, health-related quality of life, or changes in the need for pain management medication. No serious complications or major adverse events were observed. GRADE quality of evidence ranged from moderate to low. No economic evaluations were identified. Our cost-analysis revealed that GAE would result in an incremental cost of € 3432.37 per patient, requiring a health improvement of 0.137 QALY per patient to be deemed a cost-effective technology. Conclusions: In summary, based on moderate to low-certainty evidence, it remains inconclusive whether there is any difference between GAE and standard treatment for KO. However, the use of GAE would increase the costs. Larger randomized controlled trials are needed to determine the effects of using GAE for chronic pain secondary to KO and, consequently, to ascertain whether this technology could potentially become cost-effective from the NHS perspective. Resumen: Objetivo: Evaluar la efectividad, la seguridad y el coste-efectividad de la embolización de la arteria genicular (EAG) para el tratamiento de la artrosis de rodilla (AR) leve o moderada, refractaria al tratamiento habitual, o grave en personas no candidatas a cirugía. Método: Se llevó a cabo una revisión sistemática con metaanálisis y un análisis de costes para comparar la EAG y el tratamiento habitual, desde la perspectiva del Sistema Nacional de Salud (SNS) español, con un horizonte temporal de 1 año. Se estimó la mejora en salud necesaria para que la EAG se considere coste-efectiva, con un umbral de 25.000 €/año de vida ajustado por calidad (AVAC). Resultados: Se incluyeron dos ensayos controlados aleatorizados. Los resultados en dolor fueron inconsistentes y no se observaron efectos significativos en la función general, la calidad de vida ni la necesidad de medicación para el dolor. No se observaron complicaciones graves ni eventos adversos mayores. La calidad de la evidencia fue de moderada a baja. No se identificaron evaluaciones económicas previas. El coste incremental de la EAG sería de 3.432,37 €/paciente, requiriendo una mejora de 0,137 AVAC/paciente para ser coste-efectiva. Conclusiones: La evidencia de certeza moderada a baja no permite concluir si hay diferencias entre la EAG y el tratamiento habitual para la AR. Sin embargo, el uso de la EAG incrementaría los costes. Se necesitan ensayos controlados aleatorizados de mayor tamaño para determinar los efectos de la EAG en el dolor crónico secundario a la AR y establecer si podría ser coste-efectiva desde la perspectiva del SNS.